2012
DOI: 10.1177/1077558712448135
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Short-Form Learning Organization Survey

Abstract: Despite urgent need for innovation, adaptation, and change in health care, few tools enable researchers or practitioners to assess the extent to which health care facilities perform as learning organizations or the effects of initiatives that require learning. This study's objective was to develop and test a short-form Learning Organization Survey to fill this gap. The authors applied exploratory factor analysis and confirmatory factor analysis to data from Veterans Health Administration personnel to derive a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 22 publications
2
63
0
Order By: Relevance
“…Organizations may learn from frontline workers' complaints about operational problems (157), briefings and debriefings (161), incident reporting systems (86,150), and mortality and morbidity (M&M) conferences (111). Survey measures also provide organizations with opportunities to assess the extent to which they are learning organizations (139) and learn from reported events (46).…”
Section: Learning-oriented Interventionsmentioning
confidence: 99%
“…Organizations may learn from frontline workers' complaints about operational problems (157), briefings and debriefings (161), incident reporting systems (86,150), and mortality and morbidity (M&M) conferences (111). Survey measures also provide organizations with opportunities to assess the extent to which they are learning organizations (139) and learn from reported events (46).…”
Section: Learning-oriented Interventionsmentioning
confidence: 99%
“…At the organizational and systems level, LCs have potential to strengthen social networks and interorganizational learning (Bunger et al, 2014; Nembhard, 2012; Palinkas et al, 2011), leverage the influence of key opinion leaders towards improving the implementation climate for innovative practices (Wilson, Berwick, & Cleary, 2004), and foster a public and tanglible commitment from leadership (Wilson et al, 2004). By establishing mutli-disciplinary, cross-hierarchical teams, LCs may also promote increased team effectiveness (Nembhard, 2009), and can potentially build organizations’ capacity for innovation use and continuous improvement (e.g., using data to drive change and promote accountability) (Nembhard, 2012; Singer, Moore, Meterko, & Williams, 2012). …”
mentioning
confidence: 99%
“…The statements of each subscale are rated on a 7-point Likert-type scale ranging from 1 (highly inaccurate) to 7 (highly accurate), with higher scores representing perceptions of a safer environment (Psychological Safety) and greater appreciation of differences (Appreciation of Differences). In line with previous researchers (Higgins, Ishimaru, Holcombe, & Fowler, 2012;Singer, Moore, Meterko, & Williams, 2012), we adapted the language of the items to reflect the counseling program as the environment under evaluation (by replacing the word unit with program).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have noted the face validity of the LOS and reported that item derivation stemmed from decades of organizational research and a conceptual model; however, the dearth of published psychometrics (e.g., internal consistency) is a limitation (Singer et al, 2012). Higgins et al (2012), however, used three of the five Psychological Safety subscale items among a sample of teachers and found a Cronbach's alpha of .83.…”
Section: Methodsmentioning
confidence: 99%